Lifestyle and Financial Literacy Effects on Online PayLater System and Spending Behavior - Shafi Salsabil; Maria Safitri (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
The rapid growth of online paylater services has raised concerns about their impact on students’ financial behavior, particularly given the increasing prevalence of consumptive lifestyles and limited financial literacy. This study investigates the influence of Lifestyle (X1) and Financial Literacy (X2) on the use of online paylater systems (Z) and their implications for Spending Behavior (Y) among students of the Faculty of Economics and Business at Dian Nuswantoro University. The study population consisted of 2,100 students from the 2021 and 2022 cohorts, with a sample of 117 respondents determined using the Slovin formula. The sample was selected purposively based on the criteria of being 18–24 years old and active users of paylater services. Primary data were collected through an online questionnaire employing a 5-point Likert scale and analyzed using SmartPLS 3.2 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results reveal that Lifestyle has a significant positive effect on both Spending Behavior and Paylater use, while Paylater use itself also positively influences Spending Behavior. In contrast, Financial Literacy shows no significant effect and does not mediate the relationships. The novelty of this study lies in integrating Lifestyle, Financial Literacy, Paylater adoption, and Spending Behavior into a single explanatory model, thereby offering new insights into the financial decision-making patterns of Generation Z students in the context of digital financial services.